Stakeholders' perspectives of comprehensive sexuality education in Iranian male adolescences - Keshvar Samadaee Gelehkolaee; Raziyeh Maasoumi; Seyed Ali Azin; Saharnaz Nedjat; Moslem Parto; Ilia Zamani Hajiabadi (BMC, 2021)
Abstract Background A coherent sexuality education program for adolescents is part of their sexual and reproductive rights and can help them have a healthier future. Therefore, the aim of this study was to explore the perspectives and intervention preferences of Iranian stakeholders regarding comprehensive sexuality education (CSE) in male adolescents based on the IMB model (information, motivation, behavioral skills). Methods This study was a qualitative study that was analyzed through a directed content analysis approach. Individual interviews and focused group discussions (FGDs) were used for data collection. The data were collected through in-depth semi-structured interviews with stakeholders in two schools and the Education Department in Sari and the Ministry of Health and Ministry of Education in Tehran from March 2019 to August 2019. Data saturation was achieved after 28 interviews and 1 FGDs with 9 participants. Finally, two sets of data were coded and analyzed using directed content analysis. Results In this study, five themes emerged as (1) role of institutions; (2) role of organizations; (3) need for stakeholder's partnership; (4) need for adolescent sexuality socialization management; and (5) need for enhancing the teachers' professional competence, which seemed to influence the implementation of CSE in male adolescents. Participants also expressed a number of intervention preferences for CSE. The most important of these was the change in macro policies, helping to create a culture against all forms of violence and breaking the taboo of sexuality education for children and adolescents. Conclusions The results of this study revealed the need for a CSE program for adolescents' sexuality socialization. The finding showed that teachers required training to enhance their professional competence about sexuality issues. Therefore, it is necessary to design and implement culture-appropriate skill based programs to enhance the teachers' professional competence regarding the adolescents' sexual health.